2017
DOI: 10.1096/fj.201601166rr
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of thyroid hormone receptor locally in the retina is a therapeutic strategy for retinal degeneration

Abstract: Thyroid hormone (TH) signaling regulates cell proliferation, differentiation, and metabolism. Recent studies have implicated TH signaling in cone photoreceptor viability. Using mouse models of retinal degeneration, we demonstrated that antithyroid drug treatment and targeting iodothyronine deiodinases (DIOs) to suppress cellular tri-iodothyronine (T3) production or increase T3 degradation preserves cones. In this work, we investigated the effectiveness of inhibition of the TH receptor (TR). Two genes, THRA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…The finding that suppressing TH signaling protects cones in mice with normal serum TH levels suggests that there is locally elevated TH signaling in degenerating cones/retinas, the degenerating cones become more sensitive to TH, or both. We have previously shown that the expression levels of TR and Dio2 were increased in Rpe65-deficient mice (10,32). The present work showed elevated expression of the TR target genes Pdk4 and Pck2 in Rpe65 2/2 /Nrl 2/2 mice and reversal of those elevations by Dio2 heterozygous deficiency or after antithyroid treatment, supporting elevated TR transcriptional activity.…”
Section: Th Signaling Suppression-induced Cone Protection Involves Thsupporting
confidence: 76%
See 1 more Smart Citation
“…The finding that suppressing TH signaling protects cones in mice with normal serum TH levels suggests that there is locally elevated TH signaling in degenerating cones/retinas, the degenerating cones become more sensitive to TH, or both. We have previously shown that the expression levels of TR and Dio2 were increased in Rpe65-deficient mice (10,32). The present work showed elevated expression of the TR target genes Pdk4 and Pck2 in Rpe65 2/2 /Nrl 2/2 mice and reversal of those elevations by Dio2 heterozygous deficiency or after antithyroid treatment, supporting elevated TR transcriptional activity.…”
Section: Th Signaling Suppression-induced Cone Protection Involves Thsupporting
confidence: 76%
“…In the retina, TH regulates retinal development and cone opsin expression (26)(27)(28) and is associated with cone photoreceptor viability (10,(29)(30)(31)(32). Using cone degeneration mouse models, including the LCA model, Rpe65 2/2 and Rpe65 deficiency on a cone-dominant background (Rpe65 2/2 /Nrl 2/2 ) mice, we have shown that suppression of TH signaling with antithyroid drug treatment (31) or by targeting the intracellular TH components iodothyronine deiodinases (10) and thyroid hormone receptor (TR) (32) protects cones. In contrast with those findings, stimulation of TH signaling via triiodothyronine (T3) treatment or inhibition of T3 degradation was shown to cause cone death (30,31).…”
mentioning
confidence: 99%
“…2), and the functional role of these receptor subtypes [38,41]. Because THRB2 is expressed only in the cones in the retina [29,32,33], and Thrb2 deletion has been documented in cone protection against T3-induced cell death [10] and in mouse models of LCA and achromatopsia [16], we also included Thrb2 −/− mice in this study to learn more about Thrb2 deletion-associated protection in an NaIO 3 -induced mouse model of AMD. Deletion of Thrb2 protected RPE and cones, similar to that in mice with Thrb deletion.…”
Section: Discussionmentioning
confidence: 99%
“…TH signaling has also been linked to cone viability/cone degeneration. Stimulating TH signaling induces cone death [10,11], whereas suppressing TH signaling improves cone survival in mouse models of Leber's congenital amaurosis (LCA) and achromatopsia [11,12,15,16]. Of note, TH signaling has been implicated in the pathogenesis of AMD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation